ANALYSIS OF RESEARCH PAPERS PUBLISHED INTHE JOURNAL OF RESEARCH ANGRAU - A.LALITHA*, K.S. PURNIMA, M.VENKATA RAMULU, K. GURAVA REDDY and A. MANOJ (The Journal of Research ANGRAU, 2021)
This paper analysed 385 research articles comprising 263 full-length papers and 122 researchnotes published in The Journal of Research ANGRAU between 2013 and 2019 (Volumes 41-47).Themain aim of the study was to find out the impact of the Journal in terms of number of research paperspublished; subject-wise distribution of research papers, author productivity, and citation analysis ofthe Journal. Some of the important findings are: sixty-eight percent articles published were fulllengtharticles,‘Plant Sciences’ was the most published subject category, average number of citationsper volume are 545 and more than one-fourth of the articles (nearly 30 percent) published in eachvolume were from researchers of various institutes across the country. The authorship pattern istowards collaboration and maximum authors/co-authors were nine in the published seven volumes.